Adhesive sheet and adhesive sheet manufacturing method
By adding cyclic oligosaccharides to the emulsion adhesive, the problem of ultra-high molecular weight polymer diffusion forming a film in the emulsion adhesive is solved, and the adhesion durability and retention power are significantly improved.
Patent Information
- Application Number
- CN202380073471.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-09
- Filing Date
- 2023-11-09
- Publication Date
- 2025-06-03
AI Technical Summary
The ultra-high molecular weight polymer in the emulsion type adhesive diffuses to form a film after coating and drying, resulting in low coating strength, insufficient adhesion durability and retention strength.
An emulsion type adhesive containing a cyclic oligosaccharide is used to produce an emulsion type (meth)acrylate polymer by emulsion polymerization, and combined with the cyclic oligosaccharide to form an excellent adhesive layer.
The adhesion durability and retention force of the adhesive sheet are significantly improved, so that it can maintain good adhesion performance in high temperature and high humidity environments.
Smart Images

Figure CN120092058A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive sheet using an emulsion-type adhesive and a method for manufacturing the adhesive sheet. Background Art
[0002] Solvent-based adhesives are generally used for adhesive layers for various purposes. However, since the solvent in solvent-based adhesives volatilizes during coating, they are not environmentally preferred adhesives. Therefore, in recent years, a shift to water-based adhesives has been sought.
[0003] For example, Patent Document 1 discloses an adhesive composition containing an acrylic polymer emulsion and 0.01 to 1 part by weight of a silane coupling agent with respect to 100 parts by weight of the solid content of the acrylic polymer emulsion, wherein the acrylic polymer emulsion is obtained by emulsion polymerization of a monomer mixture containing 80% by weight or more of (meth)acrylate, a reactive emulsifier containing a radical polymerizable functional group, and an emulsion containing a polymerization initiator.
[0004] Prior Art Documents
[0005] Patent Documents
[0006] Patent Document 1: Japanese Patent No. 4481020 Gazette Summary of the Invention
[0007] (I) Technical Problem to be Solved
[0008] However, in emulsion-type adhesives, ultra-high molecular weight polymers diffuse after coating and drying to form a film, so there is a tendency for the film coating strength to be low. Due to this, as the adhesive layer, there are problems of low adhesive durability and low holding power.
[0009] The present invention has been completed in view of the above actual situation, and an object thereof is to provide an adhesive sheet and a method for manufacturing the adhesive sheet, which are excellent in adhesive durability and holding power.
[0010] (II) Technical Solution
[0011] In order to achieve the above object, first, the present invention provides an adhesive sheet having at least an adhesive layer, characterized in that the adhesive constituting the adhesive layer is an emulsion-type adhesive containing a cyclic oligosaccharide. The adhesive sheet of the present invention (Invention 1) has excellent adhesive durability and holding power by having the above composition and satisfying the above physical properties.
[0012] In the said invention (Invention 1), it is preferred that: the displacement amount after 70,000 seconds of measurement is less than 100 μm (Invention 2), with the adhesion strength being measured according to JIS Z0237:2009, the adhesion area being set to 25 mm × 25 mm, the temperature during the test being set to 40 °C, the placement time being set to 24 hours, and the load being set to 1 kg.
[0013] In the said inventions (Inventions 1 and 2), when the thickness of the adhesive layer is set to 600 μm and the width is set to 10 mm, in an environment of 23 °C and 50% RH, with a measurement length of 20 mm and a tensile speed of 200 mm / minute, the maximum stress at the elongation at break is preferably 9 N / mm 2 as above (Invention 3).
[0014] In the said inventions (Inventions 1 to 3), when the thickness of the adhesive layer is set to 600 μm and the width is set to 10 mm, in an environment of 23 °C and 50% RH, with a measurement length of 20 mm and a tensile speed of 200 mm / minute, the fracture energy at the elongation at break is preferably 30 MJ / m 3 as above (Invention 4).
[0015] In the said inventions (Inventions 1 to 4), the emulsion-type adhesive is preferably an emulsion-type acrylic adhesive (Invention 5).
[0016] The adhesive sheet of the said inventions (Inventions 1 to 5) may include a substrate and the adhesive layer, or may include two release sheets and the adhesive layer sandwiched by the release sheets in contact with the release surfaces of the two release sheets (Inventions 6 and 7).
[0017] Second, the present invention provides a method for manufacturing an adhesive sheet, which is a method for manufacturing the said adhesive sheet (Invention 5), characterized in that in the presence of an emulsifier, an acrylic monomer containing an (alkyl) acrylate is subjected to emulsion polymerization to produce an emulsion-type (alkyl) acrylate polymer, an emulsion-type acrylic adhesive containing the emulsion-type (alkyl) acrylate polymer and a cyclic oligosaccharide is prepared, and the emulsion-type acrylic adhesive is coated to form the adhesive layer (Invention 8).
[0018] In the present invention (Invention 8), the average particle size of the emulsion-type (alkyl) acrylate polymer is preferably 50 nm or more and 300 nm or less (Invention 9).
[0019] (III) Beneficial effects
[0020] The adhesive durability and adhesion strength of the adhesive sheet of the present invention are excellent. In addition, according to the method for manufacturing the adhesive sheet of the present invention, an adhesive sheet with excellent adhesive durability and adhesion strength can be manufactured. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a cross-sectional view of the adhesive sheet of an embodiment of the present invention.
[0022] Figure 2 is a cross-sectional view of the adhesive sheet of another embodiment of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0023] Hereinafter, embodiments of the present invention will be described.
[0024] The adhesive sheet of an embodiment of the present invention includes at least an adhesive layer, and the adhesive constituting the adhesive layer is an emulsion-type adhesive containing a cyclic oligosaccharide. The adhesive force of the adhesive sheet of this embodiment to soda-lime glass is preferably 5 N / 25 mm or more.
[0025] The adhesive sheet of this embodiment has excellent adhesion durability and holding power by having the above composition and satisfying the above physical properties. In addition, for the above adhesion durability, as an example, it can be evaluated by the peel test of the test example described later. In addition, the adhesive force in this specification basically refers to the adhesive force measured by the 180-degree peel method according to JIS Z0237:2009, and the specific test method is as shown in the test example described later.
[0026] From the viewpoints of the above adhesion durability and holding power, the adhesive force of the adhesive sheet of this embodiment to soda-lime glass is preferably greater than 5 N / 25 mm, particularly preferably 6 N / 25 mm or more, and further preferably 7 N / 25 mm or more. The upper limit of the adhesive force is not particularly limited, but reprocessability may be required. From such a viewpoint, the adhesive force is preferably 100 N / 25 mm or less, more preferably 50 N / 25 mm or less, particularly preferably 30 N / 25 mm or less, and further preferably 20 N / 25 mm or less.
[0027] According to JIS Z0237:2009, the holding force is measured by the displacement amount after 70,000 seconds of setting the adhesion area to 25 mm × 25 mm, the temperature during the test to 40 °C, the placement time to 24 hours, and the load to 1 kg. It is preferably less than 100 μm, more preferably 90 μm or less, particularly preferably 80 μm or less, and further preferably 70 μm or less. By having the above-described composition and physical properties, the pressure-sensitive adhesive sheet of the present embodiment can achieve a small displacement amount and excellent holding force. The lower limit value of the holding force (displacement amount) is most preferably 0 μm, but from the perspective of easily achieving both the above-described adhesive durability and holding force, it is preferably 8 μm or more, more preferably 16 μm or more, particularly preferably 24 μm or more, and further preferably 32 μm or more. In addition, the specific test method for the holding force in this specification is shown in the test examples described later.
[0028] When the thickness of the adhesive layer of the pressure-sensitive adhesive sheet of this example is set to 600 μm and the width is set to 10 mm, in an environment of 23 °C and 50% RH, the maximum stress when stretched to the elongation at break at a measurement length of 20 mm and a stretching speed of 200 mm / min is preferably 9 N / mm 2 or more. From the perspective that the above-described adhesive durability and holding force are further excellent and it is easy to achieve both, the maximum stress is preferably 10 to 100 N / mm 2 , more preferably 11 to 60 N / mm 2 , particularly preferably 13 to 30 N / mm 2 , further preferably 14 to 20 N / mm 2 .
[0029] When the thickness of the adhesive layer of the pressure-sensitive adhesive sheet of this example is set to 600 μm and the width is set to 10 mm, in an environment of 23 °C and 50% RH, the fracture energy when stretched to the elongation at break at a measurement length of 20 mm and a stretching speed of 200 mm / min is preferably 30 MJ / m 3 or more. From the perspective that the above-described adhesive durability and holding force are further excellent and it is easy to achieve both, the fracture energy is preferably 40 to 500 MJ / m 3 , more preferably 50 to 300 MJ / m 3 , particularly preferably 55 to 200 MJ / m 3 , further preferably 60 to 150 MJ / m 3 .
[0030] When the thickness of the adhesive of the adhesive sheet of the present embodiment is set to 600 μm and the width is set to 10 mm, in an environment of 23°C and 50% RH, when a tensile test is performed with a measurement length of 20 mm and a tensile speed of 200 mm / minute, the tensile elastic modulus is preferably 0.1 to 20 MPa, more preferably 0.3 to 16 MPa, particularly preferably 0.5 to 14 MPa, and further preferably 0.6 to 12 MPa. Thus, the above-mentioned adhesive durability and holding power can be further improved. In addition, the details of the tensile test in this specification are shown in the test examples described later.
[0031] As described above, the adhesive constituting the adhesive layer of the adhesive sheet of the present embodiment is an emulsion-type adhesive containing a cyclic oligosaccharide. Examples of the type of emulsion-type adhesive include emulsion-type acrylic adhesives, emulsion-type rubber adhesives, emulsion-type urethane adhesives, etc. From the viewpoints of adhesive durability and holding power, an emulsion-type acrylic adhesive is preferred. Hereinafter, the emulsion-type acrylic adhesive will be mainly described, but the present invention is not limited thereto.
[0032] The emulsion-type acrylic adhesive in the present embodiment preferably contains an emulsion-type (meth)acrylate polymer (A) and a cyclic oligosaccharide (B). In addition, in this specification, the term "polymer" also includes the concept of "copolymer".
[0033] 1. Each component
[0034] (1) Emulsion-type (meth)acrylate polymer (A)
[0035] The emulsion-type (meth)acrylate polymer (A) is the main adhesive component of the emulsion-type acrylic adhesive. The emulsion-type (meth)acrylate polymer (A) can be obtained by a conventional method. It is preferably obtained by emulsion polymerization of an acrylic monomer containing an alkyl (meth)acrylate. The specific method is described later. In addition, in this specification, the term "(meth)acrylic acid" refers to both acrylic acid and methacrylic acid. The same applies to other similar terms. The alkyl group can be linear or branched.
[0036] As the (meth)acrylic acid alkyl ester, from the viewpoint of adhesiveness, a (meth)acrylic acid alkyl ester having 1 to 20 carbon atoms in the alkyl group is preferred. Examples of the (meth)acrylic acid alkyl ester having 1 to 20 carbon atoms in the alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, etc.
[0037] Among them, from the viewpoint of effectively imparting adhesiveness, a (meth)acrylic acid alkyl ester having 2 to 12 carbon atoms in the alkyl group is more preferred, and a (meth)acrylic acid alkyl ester having 1 to 10 carbon atoms in the alkyl group is particularly preferred. Specifically, methyl (meth)acrylate, n-butyl (meth)acrylate or 2-ethylhexyl (meth)acrylate can be preferably cited, n-butyl acrylate or 2-ethylhexyl acrylate can be more preferably cited, and 2-ethylhexyl acrylate can be particularly preferably cited. They can be used alone or in combination of two or more.
[0038] As the (meth)acrylic acid alkyl ester, it is preferred to use a monomer having a glass transition temperature (Tg) of the homopolymer greater than 0 °C (hereinafter sometimes referred to as "high-Tg (meth)acrylic acid alkyl ester") in combination with other (meth)acrylic acid alkyl esters. Thereby, the desired cohesion can be imparted to the obtained adhesive.
[0039] Examples of the high-Tg (meth)acrylic acid alkyl ester include methyl acrylate (Tg 10 °C), methyl methacrylate (Tg 105 °C), ethyl methacrylate (Tg 65 °C), n-butyl methacrylate (Tg 20 °C), isobutyl methacrylate (Tg 48 °C), tert-butyl methacrylate (Tg 107 °C), n-stearyl acrylate (Tg 30 °C), n-stearyl methacrylate (Tg 38 °C), etc. Among them, methyl methacrylate can be preferably cited.
[0040] As the monomer unit constituting the emulsion-type (meth)acrylate polymer (A), the (meth)acrylic acid alkyl ester is preferably contained in an amount of 40 to 99.9% by mass, more preferably 55 to 99% by mass, particularly preferably 70 to 98% by mass, and further preferably 80 to 97% by mass.
[0041] As a monomer unit constituting the emulsion-type (meth)acrylate polymer (A), the high-Tg alkyl acrylate is preferably contained in an amount of 1 to 40% by mass, more preferably 5 to 30% by mass, particularly preferably 8 to 24% by weight, and further preferably 12 to 18% by weight.
[0042] As an acrylic monomer for obtaining the emulsion-type (meth)acrylate polymer (A), in addition to the above-mentioned alkyl (meth)acrylate, a functional group-containing monomer having a functional group in the molecule is preferably used. By containing this functional group-containing monomer, the obtained emulsion-type (meth)acrylate polymer (A) maintains independent particles in water due to the action of the functional group and has excellent water dispersibility.
[0043] Examples of the functional group-containing monomer may preferably include a monomer having a hydroxyl group in the molecule (hydroxyl group-containing monomer), a monomer having a carboxyl group in the molecule (carboxyl group-containing monomer), a monomer having an amino group in the molecule (amino group-containing monomer), and the like. These functional group-containing monomers may be used alone or in combination of two or more.
[0044] Among the above-mentioned functional group-containing monomers, from the viewpoint of water dispersibility, a hydroxyl group-containing monomer or a carboxyl group-containing monomer is preferred, and a carboxyl group-containing monomer is particularly preferred.
[0045] Examples of the carboxyl group-containing monomer may include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. Among them, from the viewpoint of water dispersibility, acrylic acid or methacrylic acid is preferred. They may be used alone or in combination of two or more. Particularly preferably, acrylic acid and methacrylic acid are used in combination.
[0046] As a monomer unit constituting the emulsion-type (meth)acrylate polymer (A), the functional group-containing monomer is preferably contained in an amount of 0.1 to 20% by mass, more preferably 1 to 15% by mass, particularly preferably 2 to 10% by weight, and further preferably 3 to 6% by weight.
[0047] When acrylic acid and methacrylic acid are used in combination, their blending ratio (by mass) is preferably 99:1 to 1:99, more preferably 90:10 to 10:90, particularly preferably 80:20 to 20:80, and further preferably 70:30 to 30:70.
[0048] The average particle diameter (D50) of the emulsion-type (meth)acrylate polymer (A) is preferably 50 to 300 nm, more preferably 80 to 250 nm, particularly preferably 100 to 200 nm, and further preferably 120 to 180 nm. When the lower limit value of the average particle diameter (D50) is as described above, the viscosity of the coating liquid of the adhesive can be prevented from becoming too high, and excellent coating suitability can be obtained. In addition, since a large amount of emulsifier is not required, a decrease in the durability of the adhesive can be prevented. On the other hand, when the upper limit value of the average particle diameter (D50) is as described above, the adhesive layer exhibits more excellent adhesiveness. In addition, when the average particle diameter (D50) is within the above range, the obtained adhesive exhibits more excellent cohesive force. In addition, the average particle diameter (D50) in this specification is a value measured by the dynamic light scattering method.
[0049] The content of the emulsion-type (meth)acrylate polymer (A) in the emulsion-type acrylic adhesive is preferably 60 to 99% by mass, more preferably 70 to 97% by mass, particularly preferably 80 to 96% by mass, and further preferably 90% to 95% by mass.
[0050] (2) Cyclic oligosaccharide (B)
[0051] Since the cyclic oligosaccharide (B) is usually water-soluble, its compatibility with the aqueous emulsion-type (meth)acrylate polymer (A) is excellent. Therefore, the haze value of the obtained adhesive layer can be suppressed to a low level. On the other hand, since the compatibility of the cyclic oligosaccharide (B) with the solvent-type (meth)acrylate polymer is low, when blended with the solvent-type (meth)acrylate polymer, coating cannot be performed, or even if coating can be performed, the haze value of the formed adhesive layer is quite high.
[0052] Due to its cyclic shape, polarity, etc., the cyclic oligosaccharide (B) has the property of being able to include other compounds, linear molecules, etc. However, in this embodiment, it is speculated from the radius of gyration of the emulsion-type (meth)acrylate polymer (A) that the emulsion-type (meth)acrylate polymer (A) penetrates through the cyclic oligosaccharide (B), that is, the cyclic oligosaccharide (B) does not include the emulsion-type (meth)acrylate polymer (A). Even so, the adhesive layer in this embodiment still has excellent adhesion durability and holding power.
[0053] Examples of the cyclic oligosaccharide (B) include cyclodextrin, cyclodextran, etc. The cyclic oligosaccharide (B) can be used alone or in combination of two or more.
[0054] Examples of cyclodextrin include α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, etc., among which α-cyclodextrin or γ-cyclodextrin is used.
[0055] Cyclodextran is a cyclic oligosaccharide with α-1,6 glucosidic linkages. The number of glucose units forming the ring of cyclodextran is preferably 5 to 15, particularly preferably 6 to 13, and more preferably 7 to 12.
[0056] Cyclic oligosaccharide (B) (cyclodextrin, cyclodextran) usually has hydroxyl groups, but a part or all of these hydroxyl groups can be substituted by other functional groups or modified. In addition, cyclic oligosaccharide (B) can have hydroxyl groups introduced as substituents.
[0057] With respect to 100 parts by mass of the emulsion-type (meth)acrylate polymer (A), the content of cyclic oligosaccharide (B) in the emulsion-type acrylic adhesive is preferably 0.1 to 40 parts by mass, more preferably 1 to 30 parts by mass, particularly preferably 3 to 20 parts by mass, and further preferably 5 to 10 parts by mass. Thereby, the adhesion durability and holding power are more excellent.
[0058] (3) Various additives
[0059] The adhesive P can, as needed, be added with various additives commonly used in emulsion-type adhesives or acrylic adhesives, such as silane coupling agents, ultraviolet absorbers, infrared absorbers, antistatic agents, colorants, tackifiers, antioxidants, light stabilizers, softeners, fillers, refractive index regulators, rust inhibitors, etc.
[0060] In addition, in this embodiment, it is preferred not to add crosslinking agents (thermal crosslinking agents) such as isocyanate-based crosslinking agents and epoxy-based crosslinking agents. If a crosslinking agent is added, the adhesive strength may be significantly reduced. Even if a crosslinking agent is added, with respect to 100 parts by mass of the emulsion-type (meth)acrylate polymer (A), its addition amount is still preferably 0.1 part by mass or less, particularly preferably 0.05 part by mass or less, and more preferably 0.01 part by mass or less.
[0061] In this embodiment, even without adding a crosslinking agent to the emulsion-type (meth)acrylate polymer (A), by adding cyclic oligosaccharide (B), the adhesion durability can be improved without reducing the adhesive strength.
[0062] 2. Preparation of the emulsion-type acrylic adhesive
[0063] To prepare the emulsion-type acrylic pressure-sensitive adhesive in this embodiment, first, an emulsion-type (meth)acrylate polymer (A) is produced by emulsion polymerization. Specifically, in the presence of an emulsifier, an acrylic monomer containing an alkyl (meth)acrylate is subjected to emulsion polymerization to produce an emulsion-type (meth)acrylate polymer (A). Preferably, the above acrylic monomer containing an alkyl (meth)acrylate and the emulsifier are stirred and mixed in water, heated to obtain an emulsion, and then a polymerization initiator is added, and radical polymerization is carried out while heating for emulsion polymerization.
[0064] As the emulsifier, a reactive emulsifier having a radically polymerizable functional group such as an allyl group or an allyl ether group introduced into the molecule is preferably used. For example, an anionic reactive emulsifier, a nonionic reactive emulsifier, etc. can be cited. In addition, one kind of emulsifier can be used alone, or two or more kinds can be used in combination.
[0065] Examples of the anionic reactive emulsifier include polyoxyethylene allyloxy methyl alkyl ether sulfate, polyoxyalkylene alkenyl ether sulfate, alkyl allyl sulfosuccinate, methacryloyloxy polyoxypropylene sulfate, polyoxyethylene alkyl alkenyl phenyl ether sulfate, polyoxyethylene styrenated alkenyl phenyl ether sulfate, bis(polyoxyethylene polycyclic phenyl ether) methacrylate sulfate, etc. Among them, polyoxyalkylene alkenyl ether sulfate is preferred, and ammonium polyoxyalkylene alkenyl ether sulfate is particularly preferred.
[0066] Examples of the nonionic reactive emulsifier include polyoxyethylene allyloxy methyl alkyl ether, polyoxyalkylene alkenyl ether, polyoxyethylene alkyl alkenyl phenyl ether, polyoxyalkylene alkyl phenyl ether (meth)acrylate, etc.
[0067] Based on 100 parts by mass of the total amount of the acrylic monomers, the addition amount of the emulsifier is preferably 0.1 to 10 parts by mass, particularly preferably 0.5 to 5 parts by mass, and further preferably 1 to 3 parts by mass.
[0068] The polymerization initiator is preferably a water-soluble polymerization initiator, particularly preferably a water-soluble thermal polymerization initiator. Examples of the water-soluble thermal polymerization initiator include persulfates such as potassium persulfate and ammonium persulfate, peroxides such as benzoyl peroxide and lauroyl peroxide, and azo compounds such as azobisisobutyronitrile. They can be used alone or in combination of two or more.
[0069] Based on 100 parts by mass of the total amount of the acrylic monomers, the addition amount of the polymerization initiator is preferably 0.1 to 2 parts by mass, particularly preferably 0.2 to 1 part by mass, and further preferably 0.3 to 0.5 part by mass.
[0070] The temperature for heating during emulsion preparation and polymerization is preferably 50 to 120°C, particularly preferably 60 to 90°C. In addition, the time required for polymerization is preferably 0.5 to 8 hours, particularly preferably 1 to 4 hours.
[0071] After obtaining the emulsion-type (meth)acrylate polymer (A), cyclic oligosaccharide (B) is added, and additives, water are added as needed and thoroughly mixed, whereby an aqueous emulsion-type acrylic adhesive (coating solution) can be obtained.
[0072] Regarding the concentration and viscosity that are easy to coat as prepared in this way, there is no particular limitation as long as it is within the range that can be coated, and it can be appropriately selected according to the situation. For example, it is diluted with water so that the concentration of the emulsion-type acrylic adhesive is 10 to 60% by mass.
[0073] The gel fraction of the adhesive constituting the adhesive layer of the adhesive sheet of this embodiment, particularly the emulsion-type acrylic adhesive, is preferably 50 to 99%, more preferably 55 to 95%, particularly preferably 60 to 90%, further preferably 65 to 84%, and preferably 70 to 79% among them. Thereby, the adhesion durability and holding power are further excellent.
[0074] 3. Structure of the Adhesive Sheet
[0075] The adhesive sheet of this embodiment includes at least an adhesive layer, and preferably a release sheet is laminated on one or both sides of the adhesive layer. The specific structure of an example of the adhesive sheet of this embodiment is shown in Figure 1 and Figure 2 .
[0076] As Figure 1 shown, the adhesive sheet 1A of the first embodiment is composed of a release sheet 12, an adhesive layer 11 laminated on the release surface of the release sheet 12, and a base material 13 laminated on the adhesive layer 11, starting from the bottom.
[0077] In addition, as Figure 2 shown, the adhesive sheet 1B of the second embodiment is formed by two release sheets 12a, 12b and an adhesive layer 11 sandwiched between the two release sheets 12a, 12b in contact with the release surfaces of the two release sheets 12a, 12b respectively. In addition, in this specification, the release surface of the release sheet refers to the surface having releasability in the release sheet, including the surface subjected to the release treatment and the surface showing releasability even without the release treatment.
[0078] In either of the adhesive sheets 1A and 1B, the adhesive layer 11 is composed of an emulsion-type adhesive, preferably an emulsion-type acrylic adhesive. This adhesive layer 11 is preferably formed by applying a coating solution of the emulsion-type adhesive onto a desired object and then drying it. The drying is preferably carried out by heat treatment.
[0079] The heating temperature of the heat treatment is preferably 50 to 150 °C, particularly preferably 70 to 120 °C. In addition, the heating time is preferably 10 seconds to 10 minutes, particularly preferably 50 seconds to 2 minutes.
[0080] The thickness of the adhesive layer 11 (the value measured according to JIS K7130) can be appropriately determined according to the use purpose of the adhesive sheets 1A and 1B. Usually, it is preferably 1 to 2000 μm, more preferably 5 to 1000 μm, particularly preferably 10 to 500 μm, further preferably 20 to 100 μm, and among them, it is preferably 25 to 50 μm.
[0081] There is no particular limitation on the base material 13, and all base materials that can be used as general adhesive sheets can be used. Examples include polyester films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyolefin films such as polyethylene film and polypropylene film; cellophane, diacetyl cellulose film, triacetyl cellulose film, acetyl cellulose butyrate film, polyvinyl chloride film, polyvinylidene chloride film, polyvinyl alcohol film, ethylene-vinyl acetate copolymer film, polystyrene film, polycarbonate film, polymethylpentene film, polysulfone film, polyetheretherketone film, polyethersulfone film, polyetherimide film, fluororesin film, polyamide film, acrylic resin film, polyurethane resin film, norbornene-based polymer film, cyclic olefin-based polymer film, cyclic conjugated diene-based polymer film, vinyl norbornene polymer film, etc. plastic films or their laminated films; woven or non-woven fabrics using fibers such as rayon, acrylate, and polyester; papers such as high-grade paper, glassine paper, impregnated paper, and coated paper; metal foils such as aluminum and copper; foams such as urethane foam and polyethylene foam; laminates of two or more of them, etc.
[0082] The base material 13 can be a desired optical member. Examples of the optical member include a polarizing plate (polarizing film), a polarizer, a retardation plate (retardation film), a viewing angle compensation film, a brightness enhancement film, a contrast enhancement film, a liquid crystal polymer film, a diffusion film, a semi-transmissive reflective film, etc.
[0083] The thickness of the base material 13 varies depending on its type, use, etc. Usually, it is preferably 10 to 300 μm, particularly preferably 30 to 200 μm, and further preferably 50 to 150 μm.
[0084] The release sheets 12, 12a, and 12b protect the adhesive layer 13 until the adhesive sheet 1 is used, and are peeled off when the adhesive sheet 1 (adhesive layer 11) is used.
[0085] As the release sheets 12, 12a, and 12b, for example, a polyethylene film, a polypropylene film, a polybutene film, a polybutadiene film, a polymethylpentene film, a polyvinyl chloride film, a vinyl chloride copolymer film, a polyethylene terephthalate film, a polyethylene naphthalate film, a polybutylene terephthalate film, a polyurethane film, an ethylene vinyl acetate film, an ionomer resin film, an ethylene-(meth)acrylic acid copolymer film, an ethylene-(meth)acrylate copolymer film, a polystyrene film, a polycarbonate film, a polyimide film, a fluororesin film, etc. can be used. In addition, a crosslinked film of these films can also be used. Moreover, a laminated film of these films can also be used.
[0086] Preferably, a release treatment is performed on the release surface of the release sheets 12, 12a, and 12b (especially the surface in contact with the adhesive layer 11). As the release agent used for the release treatment, for example, an alkyd-based, silicone-based, fluorine-based, unsaturated polyester-based, polyolefin-based, wax-based release agent, etc. can be cited. In addition, in the release sheets 12a and 12b, preferably one of the release sheets is a heavy release type release sheet with a large release force, and the other release sheet is a light release type release sheet with a small release force.
[0087] There is no particular limitation on the thickness of the release sheets 12, 12a, and 12b, and it is usually about 20 to 150 μm.
[0088] For manufacturing the adhesive sheet 1A, after applying the coating solution of the emulsion-type adhesive on the release surface of the release sheet 12 and performing a heat treatment to form the adhesive layer 11, the substrate 13 is laminated on the adhesive layer 11. The conditions of the heat treatment are as described above.
[0089] In addition, for manufacturing the adhesive sheet 1B, after applying the coating solution of the emulsion-type adhesive on the release surface of one release sheet 12a (or 12b) and performing a heat treatment to form the adhesive layer 11, the release surface of the other release sheet 12b (or 12a) is laminated on the adhesive layer 11.
[0090] As a method for applying the coating solution, for example, a bar coating method, a doctor blade coating method, a roller coating method, a blade coating method, a die coating method, a gravure coating method, etc. can be used.
[0091] 4. Physical properties
[0092] (1) Haze value
[0093] The haze value of the adhesive layer of the pressure-sensitive adhesive sheet of the present embodiment is preferably 10% or less, more preferably 5% or less, still more preferably 2% or less, particularly preferably 1% or less, and further preferably 0.5% or less, and preferably 0.3% or less. Thereby, the transparency is high, and it can be suitably used for optical applications (for example, for display bodies). In the present embodiment, since the water-soluble cyclic oligosaccharide (B) is blended in the aqueous emulsion type (meth)acrylate polymer (A), the compatibility is excellent, and as described above, a low haze value can be achieved. The lower limit value of the haze value of the adhesive layer is most preferably 0%, and may also be 0.1% or more. In addition, the haze value in this specification is a value measured in accordance with JIS K7136:2000.
[0094] (2) Total light transmittance
[0095] The total light transmittance of the adhesive layer of the pressure-sensitive adhesive sheet of the present embodiment is preferably 70% or more, more preferably 80% or more, particularly preferably 85% or more, and further preferably 90% or more. Thereby, the transparency is very high, and it can be suitably used for optical applications (for example, for display bodies). The upper limit value of the total light transmittance of the adhesive layer is most preferably 100%, preferably 99% or less, particularly preferably 95% or less, and further preferably 92% or less. In addition, the total light transmittance in this specification is a value measured in accordance with JIS K736 1-1:1997.
[0096] (3) CIE 1976L*a*b* color system
[0097] The chromaticity a* of the adhesive layer of the pressure-sensitive adhesive sheet of the present embodiment defined by the CIE 1976L*a*b* color system is preferably from -10 to 10, more preferably from -5 to 5, particularly preferably from -1 to 1, and further preferably from -0.3 to 0.3. By the chromaticity a* being in the above range, the hue of the adhesive layer is small, and it is particularly suitable for optical applications (for example, for display bodies).
[0098] In addition, the chromaticity b* of the adhesive layer of the pressure-sensitive adhesive sheet of the present embodiment defined by the CIE 1976L*a*b* color system is preferably from -10 to 10, more preferably from -5 to 5, particularly preferably from -1 to 1, and further preferably from -0.6 to 0.6. By the chromaticity b* being in the above range, the hue of the adhesive layer is small, and it is particularly suitable for optical applications (for example, for display bodies). In addition, the measuring methods of the chromaticity a* and b* defined by the CIE 1976L*a*b* color system in this specification are as shown in the test examples described later.
[0099] The embodiments described above are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiments also includes all design changes or equivalents within the technical scope of the present invention.
[0100] For example, the release sheet 12 in the pressure-sensitive adhesive sheet 1A can be omitted, or either one of the release sheets 12a and 12b in the pressure-sensitive adhesive sheet 1B can be omitted.
[0101] In addition, unless otherwise specified, in this specification, when "X to Y" (X and Y are arbitrary numbers) is described, it means "X or more and Y or less", and also includes the meaning of "preferably greater than X" or "preferably less than Y". Furthermore, unless otherwise specified, when "X or more" (X is an arbitrary number) is described, it includes the meaning of "preferably greater than X", and unless otherwise specified, when "Y or less" (Y is an arbitrary number) is described, it also includes the meaning of "preferably less than Y".
[0102] Examples
[0103] Hereinafter, the present invention will be described more specifically by way of examples and the like, but the scope of the present invention is not limited by these examples and the like.
[0104] [Example 1]
[0105] (1) Preparation of emulsion-type (meth)acrylate polymer
[0106] 82 parts by mass of 2-ethylhexyl acrylate, 15 parts by mass of methyl methacrylate, 2 parts by mass of methacrylic acid, 1 part by mass of acrylic acid, 1 part by mass of polyoxyalkylene alkenyl ether ammonium sulfate (manufactured by Kao Corporation, product name "LATEMUL PD-104") as a reactive emulsifier, and 80 parts by mass of distilled water were added to a four-necked flask equipped with a nitrogen inlet tube, a thermometer, a reflux condenser, and a stirring device, and stirred well and heated to 70°C. Then, 0.3 part by mass of potassium persulfate as a polymerization initiator was added, and emulsion polymerization was carried out at 70°C for 3 hours to prepare an emulsion-type (meth)acrylate polymer.
[0107] Using a dynamic light scattering type particle size distribution measuring device (manufactured by Microtrac Bell Corporation, product name: "Nanotrac Wave"), the particle size distribution of the above emulsion-type (meth)acrylate polymer was measured by the dynamic light scattering method, and the average particle size (D50) was 150 nm as a result.
[0108] (2) Preparation of emulsion-type acrylic pressure-sensitive adhesive
[0109] 100 parts by mass of the emulsion-type (meth)acrylate polymer obtained in the step (1) (in terms of solid content conversion value, the same applies hereinafter) and 5 parts by mass of α-cyclodextrin (α-CD) were mixed in water and stirred well to obtain a coating solution of the emulsion-type acrylic pressure-sensitive adhesive.
[0110] Here, Table 1 shows the respective blends (in terms of solid content conversion value) of the adhesive when the (meth)acrylate polymer (A) is set to 100 parts by mass (in terms of solid content conversion value). In addition, the details of the abbreviations and the like described in Table 1 are as follows.
[0111] [(Meth)acrylate polymer]
[0112] 2EHA: 2-Ethylhexyl acrylate
[0113] BA: n-Butyl acrylate
[0114] MMA: Methyl methacrylate
[0115] HEA: 2-Hydroxyethyl acrylate
[0116] MAC: Methacrylic acid
[0117] AAc: Acrylic acid
[0118] [Cyclic oligosaccharide]
[0119] α-CD: α-Cyclodextrin
[0120] γ-CD: γ-Cyclodextrin
[0121] CI-mix: A material mainly composed of cyclic oligosaccharide (manufactured by Nissin Sugar Manufacturing Co., Ltd., product name "CI-mix")
[0122] [Main agent form]
[0123] Em: Emulsion type
[0124] Sol: Solvent type
[0125] (3) Manufacture of the adhesive sheet
[0126] The coating solution of the emulsion-type acrylic adhesive obtained in the process of (2) is coated on the release-treated surface of the heavy-release type release sheet R1 after one side of the polyethylene terephthalate film is release-treated with a silicone-based release agent. Then, the coated layer is heat-treated at 90°C for 1 minute to form a coated layer. Next, the coated layer on the obtained release sheet R1 is adhered to the release-treated surface of the light-release type release sheet R2 after one side of the polyethylene terephthalate film is release-treated with a silicone-based release agent in such a manner that the release-treated surface of the release sheet R2 is in contact with the coated layer, to produce an adhesive sheet having an adhesive layer with a thickness of 25 μm, that is, an adhesive sheet formed of the structure of release sheet R1 / adhesive layer (thickness: 25 μm) / release sheet R2.
[0127] In addition, the thickness of the adhesive layer is a value measured using a constant-pressure thickness gauge (manufactured by TECLOCK CO., LTD., product name "PG-02") in accordance with JIS K7130. In addition, with respect to the peel strengths of the release sheets R1 and R2 in the obtained adhesive sheet, it was confirmed that the peel strength of the release sheet R1 is greater than the peel strength of the release sheet R2.
[0128] [Examples 2 to 4, Comparative Examples 1 to 2]
[0129] As shown in Table 1, the types and proportions of the respective monomers constituting the (meth)acrylate polymer and the types and blending amounts of the cyclic oligosaccharides were changed, and in addition, an adhesive sheet was produced in the same manner as in Example 1.
[0130] In addition, in Comparative Example 2, an epoxy-based crosslinking agent (manufactured by Nagase ChemteX Corporation, product name "Denacol EX-313") was blended in the amount shown in Table 1 as a crosslinking agent. In addition, in this Comparative Example 2, a curing time of 7 days was set.
[0131] The particle size distribution (average particle size (D50)) of the emulsion-type (meth)acrylate polymer produced in Examples 2 to 4 and Comparative Examples 1 to 2 was also measured in the same manner as in Example 1. The results are shown in Table 1.
[0132] [Reference Example]
[0133] 70 parts by mass of 2-ethylhexyl acrylate, 15 parts by mass of methyl methacrylate, and 15 parts by mass of 2-hydroxyethyl acrylate were copolymerized by solution polymerization to prepare a solvent-type (meth)acrylate polymer.
[0134] 100 parts by mass of the obtained solvent-type (meth)acrylate polymer was mixed with 5 parts by mass of α-cyclodextrin (α-CD) and stirred well to obtain a coating solution of a solvent-type acrylic adhesive. However, in this solvent-type acrylic adhesive, the solvent-type (meth)acrylate polymer and α-cyclodextrin are incompatible. Therefore, coating could not be performed and an adhesive layer could not be formed.
[0135] [Test Example 1] (Measurement of Gel Fraction)
[0136] The adhesive sheets produced in the examples and comparative examples were cut into a size of 80 mm × 80 mm, the adhesive layer thereof was wrapped in a polyester sieve (sieve hole size 200), and its mass was weighed with a precision balance, and the mass of the above sieve alone was subtracted to calculate the mass of the adhesive itself. The mass at this time was set as M1.
[0137] Next, the adhesive wrapped around the above-mentioned polyester screen was immersed in ethyl acetate at room temperature (23 °C) for 72 hours. Then, the adhesive was taken out and air-dried at a temperature of 23 °C and a relative humidity of 50% for 24 hours, and further dried in an oven at 80 °C for 12 hours. After drying, its mass was weighed with a precision balance, and the mass of the above-mentioned screen alone was subtracted to calculate the mass of the adhesive itself. The mass at this time was designated as M2. The gel fraction (%) is represented by (M2 / M1)×100. From this, the gel fraction (%) of the adhesive was derived. The results are shown in Table 2.
[0138] [Test Example 2] (Measurement of Adhesive Force)
[0139] The release sheet R2 was peeled off from the adhesive sheets produced in the examples and comparative examples, and the exposed adhesive layer was laminated on the easy-bonding layer of a polyethylene terephthalate (PET) film (manufactured by TOYOBO CO., LTD., product name "COSMOSHINE A4360", thickness: 100 μm) having an easy-bonding layer to obtain a laminate of release sheet R1 / adhesive layer / PET film. The obtained laminate was cut into a width of 25 mm and a length of 100 mm.
[0140] In an environment of 23 °C and 50% RH, the release sheet R1 was peeled off from the laminate, and the exposed adhesive layer was attached to a soda-lime glass plate (thickness: 1.1 mm), and pressure was applied at 0.5 MPa and 50 °C for 20 minutes in an autoclave manufactured by KURIHARA SEISAKUSHO Co., Ltd. Then, it was left at 23 °C and 50% RH for 24 hours, and then using a tensile tester (manufactured by ORIENTEC Co., Ltd., product name "TENSILON"), the adhesive force (N / 25 mm) when peeling the laminate of the PET film and the adhesive layer from the adherend was measured under the conditions of a peeling speed of 300 mm / min and a peeling angle of 180°. Conditions not described herein were measured in accordance with JIS Z0237:2009. The results are shown in Table 2.
[0141] [Test Example 3] (Measurement of Haze Value)
[0142] The adhesive layer of the adhesive sheets produced in the examples and comparative examples was laminated on glass, and it was used as a measurement sample. Based on the background measurement using glass, for the above-mentioned measurement sample, the haze value (%) was measured in accordance with JIS K7361-1:2000 using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "NDH-5000"). The results are shown in Table 2.
[0143] [Test Example 4] (Measurement of total light transmittance)
[0144] The adhesive layer of the adhesive sheet produced in the examples and comparative examples was adhered to glass, which was used as a sample for measurement. Based on the background measurement using glass, the total light transmittance (%) of the above-mentioned sample for measurement was measured in accordance with JIS K7361-1:1997 using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "NDH-5000"). The results are shown in Table 2.
[0145] [Test Example 5] (Measurement of L*a*b*)
[0146] For the adhesive sheets (the release sheets have been peeled off) produced in the examples and comparative examples, the chromaticity a* and chromaticity b* specified by the CIE1976 L*a*b* color system were measured in accordance with JIS K7136:2000 using a simultaneous photometric spectrophotometer (manufactured by Nippon Denshoku Industries Co., Ltd., product name "SQ2000"). The results are shown in Table 2.
[0147] [Test Example 6] (Tensile test)
[0148] The adhesive layers of the adhesive sheets obtained in the examples and comparative examples were laminated in multiple layers so that the total thickness was 600 μm, and then a sample with a width of 10 mm and a length of 75 mm was cut out. The sample was set on a tensile testing machine (manufactured by ORIENTEC CO., LTD., product name "TENSILON") in such a way that the measurement part of the sample was 10 mm wide and 25 mm long (elongation direction), and the sample was stretched at a tensile speed of 200 mm / minute in an environment of 23°C and 50% RH using this tensile testing machine. The sample was stretched until it broke, and the maximum stress (N / mm 2 ) and the breaking energy (MJ / m 3 ) at this time were measured. In addition, the tensile elastic modulus (MPa) was measured through the above tensile test. The respective results are shown in Table 2.
[0149] [Test Example 7] (Measurement of holding force)
[0150] Except for the operations shown below, the holding force of the adhesive sheet was measured in accordance with JIS Z0237:2009. The adhesive sheets obtained in the examples and comparative examples were cut into a size of 25 mm × 125 mm, the release sheet R2 was peeled off, and only the adhesive layer of the 25 mm × 25 mm portion of the adhesive sheet was attached to a stainless steel plate (SUS304 #360). Thereafter, the stainless steel plate was set perpendicular to the ground and the adhesive sheet was suspended from the stainless steel plate, and it was left at 40 °C for 15 minutes. Thereafter, a load of 1 kg was applied and it was left at 40 °C for 24 hours, and the displacement amount (μm) of the adhesive sheet after 70,000 seconds was measured. The results are shown in Table 2.
[0151] [Test Example 8] (Evaluation of Adhesive Durability)
[0152] The release sheet R2 was peeled off from the adhesive sheets produced in the examples and comparative examples, and the exposed adhesive layer was bonded to the adhesive layer of a PET film (manufactured by TOYOBO CO., LTD., product name “COSMOSHINE A4360”, thickness: 100 μm) having an adhesive layer to obtain a laminate of release sheet R1 / adhesive layer / PET film. The obtained laminate was cut into a width of 50 mm and a length of 100 mm.
[0153] In an environment of 23 °C and 50% RH, the release sheet R1 was peeled off from the laminate, the exposed adhesive layer was attached to a soda-lime glass plate (thickness: 1.1 mm), and it was set vertically. Thereafter, the upper end of the adhesive sheet was peeled off by 2 cm and punched with a puncher. A 1 kg load was suspended using a thin string passing through this hole, and the behavior of the adhesive sheet peeling from the soda-lime glass plate was observed. Then, based on the following criteria, the adhesive durability was evaluated. The results are shown in Table 2.
[0154] ○: The peeled end did not move until 1 minute later.
[0155] ×: Peeling occurred within 1 minute.
[0156] [Test Example 9] (Evaluation of Flexural Durability)
[0157] Under the environment of 23°C and 50% RH, the release sheet R2 was peeled off from the adhesive sheets manufactured in the examples and comparative examples, and the exposed adhesive layer was laminated on the adhesion-promoting layer of a PET film (manufactured by TOYOBO CO., LTD., product name "COSMOSHINE A4360", thickness: 100 μm) with an adhesion-promoting layer as the substrate. After that, the release sheet R1 was peeled off, and the exposed adhesive layer was laminated on the same PET film as the substrate in the same manner. After that, it was pressurized in an autoclave manufactured by KURIHARA SEISAKUSHO Co., Ltd. at 0.5 MPa and 50°C for 20 minutes, and then left for 24 hours under the conditions of 23°C and 50% RH. The laminate composed of a PET film (substrate) / adhesive layer / PET film (substrate) obtained in this way was cut into 150 mm × 50 mm and used as a sample.
[0158] The obtained sample was flexed 100,000 times at a flexure diameter with a stroke of 80 mm and a flexure speed of 30 rpm under the environment of 23°C and 50% RH. After that, the end portions in the length direction of the sample were observed with a digital microscope, and the displacement amounts of both end portions of the adhesive layer relative to the substrate were measured respectively. Based on the total value of the displacement amounts of both end portions, the dimensional change rate (%) of the end portion of the adhesive layer relative to the substrate length was calculated. In addition, the lifting and peeling of the flexure portion in the sample were visually confirmed. After that, based on the following criteria, the flexure durability (including the concept of adhesion durability) was evaluated. The results are shown in Table 2.
[0159] ○: There is no lifting or peeling at the flexure portion, and the end portion dimensional change rate is within 5%.
[0160] △: There is no lifting or peeling at the flexure portion, and the end portion dimensional change rate is greater than 5%, or there is lifting at the flexure portion, and the end portion dimensional change rate is within 5%.
[0161] ×: There is peeling at the flexure portion, and the end portion dimensional change rate is greater than 5%.
[0162] [Table 1]
[0163]
[0164] [Table 2]
[0165]
[0166] As can be seen from Table 2, the adhesion durability (including flexure durability) and holding power of the adhesive sheets obtained in the examples are excellent.
[0167] Industrial Applicability
[0168] The adhesive sheet of the present invention can be used for various applications including, for example, optical applications. In addition, it can also be suitably used for devices that are repeatedly flexed.
[0169] Explanation of reference numerals
[0170] 1A, 1B: Adhesive sheet; 11: Adhesive layer; 12, 12a, 12b: Release sheet; 13: Substrate.
Claims
1. An adhesive sheet which is an adhesive sheet having at least an adhesive layer, Characterized in that, The adhesive constituting the adhesive layer is an emulsion-type adhesive containing a cyclic oligosaccharide, and the adhesive force of the adhesive sheet to soda-lime glass is 5 N / 25 mm or more.
2. The adhesive sheet according to claim 1, Characterized in that, The displacement amount after 70,000 seconds measured by the holding force according to JIS Z0237:2009 with the adhesion area set to 25 mm × 25 mm, the temperature during the test set to 40 °C, the standing time set to 24 hours, and the load set to 1 kg is less than 100 μm.
3. The adhesive sheet according to claim 1, Characterized in that, When the thickness of the adhesive layer is set to 600 μm and the width is set to 10 mm, the maximum stress at the elongation at break when stretched at a measurement length of 20 mm and a stretching speed of 200 mm / minute in an environment of 23°C and 50% RH is 9 N / mm 2 or more.
4. The adhesive sheet according to claim 1, Characterized in that, When the thickness of the adhesive layer is set to 600 μm and the width is set to 10 mm, the fracture energy at the elongation at break when stretched to the elongation at break at a measurement length of 20 mm and a tensile speed of 200 mm / minute in an environment of 23°C and 50% RH is 30 MJ / m 3 or more.
5. The adhesive sheet according to claim 1, Characterized in that, The emulsion-type adhesive is an emulsion-type acrylic adhesive.
6. The adhesive sheet according to claim 1, Characterized in that, It has a base material and the adhesive layer.
7. The adhesive sheet according to claim 1, Characterized in that, It has two release sheets and the adhesive layer sandwiched by the release sheets in contact with the release surfaces of the two release sheets.
8. A method for manufacturing an adhesive sheet which is a method for manufacturing the adhesive sheet according to claim 5, Characterized in that, In the presence of an emulsifier, an acrylic monomer containing an alkyl (meth)acrylate is subjected to emulsion polymerization to produce an emulsion-type (meth)acrylate polymer, Prepare an emulsion-type acrylic adhesive containing the emulsion-type (meth)acrylate polymer and a cyclic oligosaccharide, Coat the emulsion-type acrylic adhesive to form the adhesive layer.
9. The method for manufacturing an adhesive sheet according to claim 8, Characterized in that, The average particle size of the emulsion-type (meth)acrylate polymer is 50 nm or more and 300 nm or less.